Brazilian Thalassemia Association protocol for iron chelation therapy in patients under regular transfusion - Verissimo,Monica Pinheiro de Almeida (2013)
In the absence of an iron chelating agent, patients with beta-thalassemia on regular transfusions present complications of transfusion-related iron overload. Without iron chelation therapy, heart disease is the major cause of death; however, hepatic and endocrine complications also occur. Currently there are three iron chelating agents available for continuous use in patients with thalassemia on regular transfusions (desferrioxamine, deferiprone, and deferasirox) providing good results in reducing cardiac, hepatic and endocrine toxicity. These practice guidelines, prepared by the Scientific Committee of Associação Brasileira de Thalassemia (ABRASTA), presents a review of the literature regarding iron overload assessment (by imaging and laboratory exams) and the role of T2* magnetic resonance imaging (MRI) to control iron overload and iron chelation therapy, with evidence-based recommendations for each clinical situation. Based on this review, the authors propose an iron chelation protocol for patients with thalassemia under regular transfusions.